2021
DOI: 10.1177/19485506211053564
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gendered Entitlement in Understanding Inequality in the Bedroom

Abstract: Five studies (using U.S. samples) examined whether men’s higher entitlement contributes to a sexual pleasure gap that disadvantages women. Participants indicated that men receive more sexual pleasure from their partners, whereas women provide more pleasure (Study 1a). Participants believed that men have more of a right to experience orgasm in both hook-up and relationship encounters and attributed higher negative affect to the male target than to the female target when the target did not experience an orgasm i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…Ungerechte und unnötige Orgasmus-Lücken beim Heterosex zugunsten der sexuellen Lust von Frauen zu schließen, würde nicht nur dem Wohlbefinden und der Beziehungsqualität zugutekommen, sondern könnte -wie neuerdings diskutiert wird -möglicherweise auch einen positiven Einfluss auf das sexuelle Verlangen von Frauen haben (Klein and Conley 2021;Peragine et al 2022).…”
Section: Aktuelle Wissenschaftliche üBersichtsarbeitenunclassified
“…Ungerechte und unnötige Orgasmus-Lücken beim Heterosex zugunsten der sexuellen Lust von Frauen zu schließen, würde nicht nur dem Wohlbefinden und der Beziehungsqualität zugutekommen, sondern könnte -wie neuerdings diskutiert wird -möglicherweise auch einen positiven Einfluss auf das sexuelle Verlangen von Frauen haben (Klein and Conley 2021;Peragine et al 2022).…”
Section: Aktuelle Wissenschaftliche üBersichtsarbeitenunclassified
“…Participants argued that many men do not care about their partners' orgasm (21.6%) or are unaware of how to bring their partners to orgasm (12.1%). Research has found that young men and women both report men's disregard for women's pleasure during casual sex (Armstrong et al, 2012) and report that men have greater entitlement to orgasm (Klein & Conley, 2021). As such, the "men don't care" code appears to capture a real-life experience, particularly for undergraduate students in a hookup context.…”
Section: Orgasm Gap Perceptionsmentioning
confidence: 99%
“…There are several theories as to why this orgasm disparity exists, including a cultural overvaluing of vaginal intercourse (i.e., the "coital imperative"), insufficient clitoral stimulation, prioritization of men's pleasure and orgasm over women's (i.e., the "male orgasmic imperative"), a general lack of knowledge and education on how women reliably achieve orgasm, and sexual objectification (Armstrong et al, 2012;Conley et al, 2011;Gusakova et al, 2020;Klein & Conley, 2021;Mahar et al, 2020;Mintz, 2017;Wade, 2015;Wade et al, 2005;Willis et al, 2018). Yet, no research up to this point has examined how women and men themselves understand the mechanisms underlying these gender differences in orgasm frequency.…”
mentioning
confidence: 99%
“…Sexual norms such as “men’s orgasm signals the end of sex” (Braun et al., 2003 ; Muehlenhard & Shippee, 2010 ; Opperman et al., 2014 ) and “men are the source of (or responsible for) female orgasm” (Fahs, 2011 ; Muehlenhard & Shippee, 2010 ; Salisbury & Fisher, 2014 ) are some of the sexual beliefs that might influence ideas about what are “acceptable” sexual behaviors in mixed-sex relationships. However, established sociocultural sexual scripts often overvalue penile-vaginal intercourse (PVI) and male pleasure (over women’s pleasure) (Klein & Conley, 2022 ; Laan et al., 2021 ; Mahar et al., 2020 ; Mintz, 2017 ), and only include these sexual behaviors: kissing, partner touching, oral genital contact, PVI, women’s orgasm (real or “faked”), and men’s orgasm (real) which indicates sex is over (Braun et al., 2003 ; Gagnon & Simon, 1987 ; Muehlenhard & Shippee, 2010 ).…”
Section: Introductionmentioning
confidence: 99%